Inovasi Pelayanan Wakaf Produktif Era Digital: Studi Kasus Di Yayasan Wakaf Bani Umar 2018 - Syaifullah, Hamli; Idrus, Ali (UIN Sunan Kudus, 2019)
This study wants to find out the role of digital-based services performed by Nadzir in carrying out waqf management activities. This research uses a case study at the Wakaf Bani Umar Foundation, a foundation that focuses on managing productive waqf. In analyzing data, researchers used a qualitative descriptive analysis. From this study three conclusions were obtained, including: 1). Management of waqf assets must be profit oriented, 2). Nadzir must provide the best service, 3). Nadzir must be consistent in using social media as a form of digital-based services.